Comparison of ImageJ Software Results Between The Growth of Lemna minor in the Presence of Sodium Bicarbonate and Without Sodium Bicarbonate - lukas kristian; runita rizkiyanti putri; tutun nugraha (Liaison Journal of Engineering, 2022)
Water quality in the recent years had been a very important aspect in daily life, especially in big cities where they produced many liquid organic waste. One of a way to overcome this problem, a primary biological treatment could be used to transform this liquid organic waste water to become a cleaner water by using certain plant that belong to family of duckweeds, which was Lemna minor. Lemna minor plant had the benefit from growing on top of polluted water, in addition it helped to induce a better quality of the polluted by the reducing organic matters. The organic matters itself could be dangerous for daily usage, but for the Lemna minor it was useful for their growth due to their unique ability. The ability that was used by this Lemna minor was called as phytoremediation which defined as the ability to absorb some excess organic matters and transform it to become a nutrients for the plant growth. In this experiment, the phytoremediation effect would be observed by the growth of the plant inside a home scale bioreactors and the result was compared by using ImageJ Software analysis. The comparison are done between two aquariums that were filled with and without sodium bicarbonate. During the experiment days without the sodium bicarbonate, some ofthe Lemna minor could grow very well, but some of the Lemna minor also could not grow very well. During the experiment days with sodium bicarbonate was added, the plant growth was more consistent and grown very well due to the effect of the pH stability and alkalinity return properties. The percent coverage area when the Lemna minor grown very well, it reached up to 66 %.Keywords: Template; Lemna minor, ImageJ, Bioreactor, Waste water treatment, Sodium bicarbonate